Strategi Bisnis UMKM Berbasis E-Commerce Pada Online Shop Adiva Shakila - Riza, Chiko Muhamad; Suwarsinah, Heny Kuswanti; Sahara (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
Digital transformation is an urgency for micro, small and medium enterprises (MSMEs) in facing global challenges. The benefits of digital transformation through the application of e-commerce include entering the global market, increasing productivity and efficiency. Adiva Shakila Perlengkapan Bhayangkari dan Organisasi (ASPBO) is an e-commerce-based MSME that experienced a decline in profits throughout 2020 and 2021. The purpose of this study is to analyze the factors that affect the decline in APSBO performance, formulate business strategies that are in accordance with the external and internal environment ASPBO, and determine priority strategies that can be implemented by ASPBO. The selection of respondents was carried out using the purposive sampling method with the assumption that the respondent's knowledge of the object of study. The analytical tools used in this research are internal factor evaluation, external factor evaluation, strength weakness opportunity threat, and quantitative strategic planning matrix. The results of this study indicated that social restrictions are the main threat, the unemployment rate in the textile and textile product industry is the main opportunity, a good reputation is the main strength, and the disruption of product supply is the main weakness. The results also showed that there are four strategy formulations with the first priority, namely empowering the surrounding community who have expertise in the garment sector as an alternative supplier, the second priority is the evaluation and efficiency of business activities, the third priority is sales promotion through the provision of discounts and online advertising, and the fourth priority. namely increasing consumer loyalty. Keywords: e-commerce, MSMEs, QSPM, strategy formulation, SWOT